Models of Concurrent Disorder Service: Policy, Coordination, and Access to Care - Wiktorowicz, Mary; Abdulle, Aber; Di Pierdomenico, Kaitlin; Boamah, Sheila A. (Frontiers in Psychiatry, 2019)
Background: Societal capacity to address the service needs of persons with concurrent mental health and substance-use disorders has historically been challenging given a traditionally siloed approach to mental health and substance-use care. As different approaches to care for persons with concurrent disorders emerge, a limited understanding of current models prevails. The goal of this paper is to explore these challenges along with promising models of coordinated care across Canadian provinces. Materials and methods: A scoping review of policies, service coordination and access issues was undertaken involving a review of the formal and gray literature from 2000 to 2018. The scoping review was triangulated by an analysis of provincial auditor general reports. Results: Models of concurrent disorders service were found to have evolved unevenly. Challenges related to the implementation of models of collaborative care and local networks that foster service coordination and policy accountability were found to inhibit integrated care. Conclusion: Emergent models of coordinated care were found to include collaborative care, regional networks with centralized access to care, clinical information-sharing, cross-training, improved scope of care to include psychologists and alignment of physician incentives with patient needs to better support patient care.